Mixing and Compaction Temperature of Nanosilica Composite Polymer Modified Asphalt - Esraa J Al-mousawi; Rashaa H Al-Rubaee; Ammar A Shubber (Wasit Journal of Engineering Sciences)
Recently, polymer -nanocomposites were used to manufacture durable asphalt mixtures to replace the polymer modified binder, because of the remarkable properties and unique features of nanomaterials compared to conventional materials, such as their wide surface area and small dimensions, making it possible to be utilized as an additive for asphalt paving. Nanosilica particles (NS) are one of the latest minerals which likely integrate useful characteristics, such as huge surface area, good distributions, high absorption levels, high stability, and a high level of purity. Therefore, this paper is interested in studying the characteristics of nanocomposite-polymer modified asphalt. In laboratory work, a pure asphalt 60-70 penetration grade, has been modified separately with waste polypropylene polymer (WPP), and nanosillica composite polypropylene (NS/WPP) at different concentrations. As a result, two modified binders: waste polypropylene polymer- modified asphalt (WPP-MA), and nanosillica composite polypropylene modified asphalt (NSCPMA) were obtained. Traditional asphalt binder tests were performed for pure and modified binders such as penetration, ductility, flash and fire point test, softening point, and rotational viscosity. Also, storage stability test has been conducted to ensure the storage stability of binders at high temperatures. The results showed an improvement in physical properties and increase in mixing and compaction temperature due to the increase in stiffness of (NSCPMA). The results also indicated that the nanosillica composite polypropylene modified asphalt binders have good storage stability at high temperatures.